2020
DOI: 10.1039/d0ra00324g
|View full text |Cite
|
Sign up to set email alerts
|

N-Fluorobenzenesulfonimide: a useful and versatile reagent for the direct fluorination and amination of (hetero)aromatic C–H bonds

Abstract: This review updates recent advances and developments in the direct fluorination and amination of (hetero)aromatic C–H bonds utilizing N-fluorobenzenesulfonimide, classified according to the type of catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…Here, NFSI 23 shows practicable reactivity towards aldehyde substrates in the presence of an organocatalyst, and this is also mirrored by its many synthetic applications in metal catalysed reactions. 142,143 In 2020, Cornella et al 144 reported the electrophilic fluorination of arylboronic esters enabled by bismuth redox catalysis. The reactivities of several N−F reagents with phenylbismine 167 were investigated ( 144 Yields were determined by 19 F NMR spectroscopic analysis of crude reactions using 1-fluoro-4-nitrobenzene as an internal standard.…”
Section: Qualitative Reactivities In Synthetic Studiesmentioning
confidence: 99%
“…Here, NFSI 23 shows practicable reactivity towards aldehyde substrates in the presence of an organocatalyst, and this is also mirrored by its many synthetic applications in metal catalysed reactions. 142,143 In 2020, Cornella et al 144 reported the electrophilic fluorination of arylboronic esters enabled by bismuth redox catalysis. The reactivities of several N−F reagents with phenylbismine 167 were investigated ( 144 Yields were determined by 19 F NMR spectroscopic analysis of crude reactions using 1-fluoro-4-nitrobenzene as an internal standard.…”
Section: Qualitative Reactivities In Synthetic Studiesmentioning
confidence: 99%
“…In the search for solid reagents compatible with mechanochemical techniques, we became interested in evaluating the behavior of N -fluorobenzenesulfonimide (NFSI) under ball-milling conditions. NFSI is a colorless crystalline powder (mp 114–116 °C), bench-stable, and an easy-to-handle reagent, which, due to its commercial availability, has been extensively used as a fluorinating agent in solution [ 7 9 ]. Additionally, NFSI has also been explored as an oxidant, amidation reagent [ 9 11 ], and phenylsulfonyl group transfer reagent [ 12 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…NFSI is a colorless crystalline powder (mp 114–116 °C), bench-stable, and an easy-to-handle reagent, which, due to its commercial availability, has been extensively used as a fluorinating agent in solution [ 7 9 ]. Additionally, NFSI has also been explored as an oxidant, amidation reagent [ 9 11 ], and phenylsulfonyl group transfer reagent [ 12 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The electrophilic fluorination of aromatic heterocycles has been less studied than the fluorination of arenes. However, a number of fluoropyrroles [ 4 , 5 ], furans [ 6 ], thiophenes [ 7 ], pyrrolo[2,3-d]pyrimidines [ 8 , 9 ], quinolines [ 10 , 11 , 12 ] and indoles [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] have been prepared either by direct fluorination or by fluorodecarboxylation using mainly Selectfluor ® and N -fluorobenzenesulfonimide.…”
Section: Introductionmentioning
confidence: 99%